HUBUNGAN KONDISI FISIK RUMAH DENGAN PENYAKIT ISPA PADA BALITA DI DESA PAYA MABAR KECAMATAN TEBING TINGGI KABUPATEN SERDANG BEDAGAI TAHUN 2022 - Helfi Nolia Tambunan; Susiati Saragih; Erba Kalto Manik (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Acute respiratory infection (ARI) is one of the main causes of death by killing ± 4 million children under five each year. There were 108 cases of acute respiratory infection in Paya Mabar Village. This study aims to determine the relationship between the physical condition of the house and respiratory disease in toddlers in Paya Mabar Village, Tebing Tinggi District, Serdang Bedagai Regency in 2022. This type of research is an analytical survey with a cross sectional approach. The sampling technique used was purposive sampling, where the number of samples was 52 respondents. The data analysis technique used the chi-square statistical test. The results showed that there was a relationship between occupancy density (p=0.042), OR(0.618), CI(0.202-1.887), wall type (p=0.012), OR(1.000), CI( 0.275-3.643), Floor type (p=0.000), OR(0.071), CI(0.019-0.272), Roof (p=0.041), OR(1.406), CI(0.446-4.432), (p=0.026) , OR(0.230), CI(0.071-0.744), and Humidity (p=0.001), OR(9.048), CI(2.571-31.842) on ISPA Disease in toddlers. The most dominant variable was humidity with OR(9.048). Therefore, it is suggested to people who have toddlers to improve the condition of the physical environment of the house, open ventilation so that there is a change of air to avoid high humidity, always clean the home environment to prevent ARI in toddlers.